2011
DOI: 10.1007/jhep11(2011)073
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational contributions to gauge Green’s functions and asymptotic free power-law running of gauge coupling

Abstract: We perform an explicit one-loop calculation for the gravitational contributions to the two-, threeand four-point gauge Green's functions with paying attention to the quadratic divergences. It is shown for the first time in the diagrammatic calculation that the Slavnov-Taylor identities are preserved even if the quantum graviton effects are included at one-loop level, such a conclusion is independent of the choice of regularization schemes. We also present a regularization scheme independent calculation based o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
(63 reference statements)
1
7
0
Order By: Relevance
“…Although different in a form, this gravitational correction leads to the same conclusions as those drawn by Robinson and Wilczek [27]. This result has been also derived by Ho et al [35] in momentum subtraction scheme and corrected by Tang and Wu [36,37] in the loop regularization scheme. The power law correction has been criticized by may authors.…”
Section: Introductionsupporting
confidence: 83%
“…Although different in a form, this gravitational correction leads to the same conclusions as those drawn by Robinson and Wilczek [27]. This result has been also derived by Ho et al [35] in momentum subtraction scheme and corrected by Tang and Wu [36,37] in the loop regularization scheme. The power law correction has been criticized by may authors.…”
Section: Introductionsupporting
confidence: 83%
“…[11,12] is an ideal regularization scheme in studying both theoretical and phenomenological properties of SUSY and softly broken SUSY. LORE is believed to be able to preserve various symmetries, including Poincare symmetry, gauge symmetry, SUSY, etc, 2 and has already been applied in several studies, such as the one-loop renormalization of Non-Abelian gauge theories [13], the study of composite Higgs model [14], the gravitational corrections to the running of gauge couplings [15][16][17], the renormalization of supersymmetric field theories [18], the trace anomaly in quantum electrodynamics (QED) [19], the diphoton channel of the Higgs decay [20], the quadratic running of the effective Higgs mass parameter. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Gravitational contributions on the running of gauge coupling in the Einstein-Yang-Mills theory were also calculated in Refs. [31,32], where the authors compared different regularization schemes and found that, while dimensional regularization leads to no gravitational contribution at one-loop, the use of loop regularization leads to a nonzero contribution that is proportional to µ 2 . They claim that, although the Slavnov-Taylor identities are satisfied irrespective of the regularization scheme used, the gravitational correction for beta function is scheme-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…As we can see from eqs. (17a),(20a),( 22),( 24),( 26),( 29), (32), the Slavnov-Taylor identities are respected, since we have…”
Section: The One-loop Renormalizationmentioning
confidence: 99%